Chemically Controlled Helical Polymorphism in Protein Tubes by Selective Modulation of Supramolecular Interactions - Li, Zhen; Chen, Shuyu; Gao, Chendi; Yang, Zhiwei; Shih, Kuo-Chih; Kochovski, Zdravko; Yang, Guang; Gou, Lu; Nieh, Mu-Ping; Jiang, Ming; Zhang, Lei; Chen, Guosong (Journal of the American Chemical Society, 2019)
Polymorphism has been the subject of investigation across different research disciplines. In biology, polymorphism could be interpreted in such a way that discrete biomacromolecules can adopt diversiform specific conformations/packing arrangement, and this polymorph-dependent property is essential for many biochemical processes. For example, bacterial flagellar filament, composed of flagellin, switches between different supercoiled state allowing the bacteria to swim and tumble. However, in artificial supramolecular systems, it is often challenging to achieve polymorph control and prediction, and in most cases, two or more concomitant polymorphs of similar formation energies coexist. Here, we show that a tetrameric protein with properly oriented binding sites on its surface can arrange into diverse protein tubes with distinct helical parameters by adding specifically designed inducing ligands. We examined several parameters of the ligand that would influence the protein tube formation and found that the flexibility of the ligand linker and the dimerization pose of the ligand complex is critical for the successful production of the tubes and eventually influence the specific helical polymorphs of the formed tubes. A surface lattice accommodation model was further developed to rationalize the geometrical relationship between each helical tube type. Molecular simulation was used to elucidate the interactions between ligands and SBA and molecular basis for polymorphic switching of the protein tubes. Moreover, the kinetics of structural formation was studied and the ligand design was found that can affect the kinetics of the protein polymerization pathway. In short, our designed protein tubes serves as an enlightening system for understanding how a protein polymer composed of a single protein switches among different helical states.